ESGO-ESTRO-ESP guidelines for the management of patients with endometrial carcinoma: update 2025 - Concin, Nicole; Matias-Guiu, Xavier; Cibula, David; Colombo, Nicoletta; Creutzberg, Carien L; Ledermann, Jonathan; Mirza, Mansoor Raza; Vergote, Ignace; Abu-Rustum, Nadeem R; Bosse, Tjalling; Chargari, Cyrus; Espenel, Sophie; et al. (The Lancet. Oncology, 2025)
In 2023, based on advances in the understanding of the pathological and molecular features of endometrial carcinoma, an updated International Federation of Gynaecology and Obstetrics (FIGO) staging system was published, aiming to better define prognostic groups and identify relevant treatment subgroups by including factors reflecting tumour biology (histological subtypes, lymphovascular space invasion, and molecular classification) alongside refinements of anatomical factors (peritoneal carcinomatosis and lymph node metastasis). As part of its mission to improve the quality of care for people with gynaecological cancers, the European Society of Gynaecological Oncology (ESGO), European Society for Radiotherapy and Oncology (ESTRO), and the European Society of Pathology (ESP) updated the ESGO-ESTRO-ESP evidence-based guidelines published in 2021 by incorporating this revised FIGO staging and the large body of new evidence addressing the management of endometrial carcinoma. The development process of these guidelines was based on a systematic literature review and critical appraisal process involving an international multidisciplinary development group consisting of 30 experts from relevant disciplines (gynaecological oncology, radiation oncology, medical oncology, and pathology). A patient representative was also included. Before publication, the guidelines were reviewed by 225 independent international practitioners in cancer care delivery and three patient representatives from Asia, Europe, North Africa, North America, the Middle East, and South America to ensure a global perspective. These guidelines comprehensively cover diagnosis, management, follow-up, and patient education. Management includes surgical and adjuvant therapy according to the stage of the disease, and metastatic and recurrent disease. The management algorithms and the principles of radiotherapy and pathological evaluation are also defined.
Keywords: Humans; Medical Oncology; Neoplasm Staging; ženské pohlaví; lidé; lékařská onkologie; Systematic Reviews as Topic; nádory endometria; Female; systematický přehled jako téma; staging nádorů; Endometrial Neoplasms